The Meteoric Ni Layer in the Upper Atmosphere. Issue 8 (11th August 2020) - Daly, Shane M.; Feng, Wuhu; Mangan, Thomas P.; Gerding, Michael; Plane, John M. C.
Abstract: The first global atmospheric model of Ni (WACCM‐Ni) has been developed to understand recent observations of the mesospheric Ni layer by ground‐based resonance lidars. The three components of the model are: the Whole Atmospheric Community Climate Model (WACCM6); a meteoric input function derived by coupling an astronomical model of dust sources in the solar system with a chemical meteoric ablation model; and a comprehensive set of neutral, ion‐molecule, and photochemical reactions pertinent to the chemistry of Ni in the upper atmosphere. In order to achieve closure on the chemistry, the reaction kinetics of three important reactions were first studied using a fast flow tube with pulsed laser ablation of a Ni target, yielding k (NiO + O) = (4.6 ± 1.4) × 10 −11, k (NiO + CO) = (3.0 ± 0.5) × 10 −11, and k (NiO2  + O) = (2.5 ± 1.2) × 10 −11  cm 3 molecule −1  s −1 at 294 K. The photodissociation rate of NiOH was computed to be J (NiOH) = 0.02 s −1 . WACCM‐Ni simulates satisfactorily the observed neutral Ni layer peak height and width, and Ni + measurements from rocket‐borne mass spectrometry. The Ni layer is predicted to have a similar seasonal and latitudinal variation as the Fe layer, and its unusually broad bottom‐side compared with Fe is caused by the relatively fast NiO + CO reaction. The quantum yield for photon emission from the Ni + O3 reaction, observed in the nightglow, is estimated to be between 6% and 40%. Plain Language Summary: Around 30 t of cosmic dust particles enters the Earth's atmosphere every day. A fraction of these particles heat through collisions with air molecules to the point where they melt and evaporate. This process of ablation injects a variety of metals into the region between 80 and 110 km, where the metals occur globally as layers of atoms and ions. The metal Ni is present in cosmic dust in metallic grains as an alloy with Fe. In the past decade, the layer of Ni atoms has been observed for the first time, complementing earlier measurements from rockets of Ni + ions, and a faint contribution to the Earth's nightglow from excited NiO molecules. In this study we present the first atmospheric model of nickel, which is possible following an extensive laboratory program to measure the rates of the reactions that Ni species are likely to undergo in the upper atmosphere, as well as the ablation of Ni from meteoritic fragments. The model successfully simulates the observed layers of Ni and Ni + and shows that the production of photons from the reaction between Ni and O3 must be relatively efficient. Key Points: First atmospheric model of meteor‐ablated Ni in the upper atmosphere simulates the Ni and Ni + layers with good fidelity Laboratory work on the reactions of NiO with CO and O shows that the unusually broad Ni layer is caused by the fast CO reaction The reaction between Ni and O3 contributes emission from electronically excited NiO to the airglow, with a quantum yield of 6–40%